PENGARUH KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN KANTOR BADAN PENANAMAN MODAL DAN PELAYANAN PERIZINAN TERPADU (BPMP2T) KOTA MATARAM - Rupawan, Doddy (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This study is aimed to determine the significance of the effect of: (1) the organizations commitment to the productivity of office workers BPMP2T Mataram, (2) job satisfaction on the productivity of office workers BPMP2T Mataram, (3) organizational commitment and job satisfaction on the productivity of office workers BPMP2T City Mataram. The population in this study was all employees of the BPMP2T Mataram City office. Based on the limited population, this study was using census method. Based on the results of research and discussion on the influence of organizational commitment and job satisfaction on employee productivity office of Board of Investment and Integrated Licensing Services (BPMP2T) Mataram, it can be concluded: (a). There was the influence of Organizational Commitment to employee productivity BPMP2T office City Mataram. (B). There was the influence of job satisfaction on employee productivity BPMP2T office City Mataram. (C). There was the influence of Organizational Commitment and Job Satisfaction of the productivity of office workers BPMP2T City Mataram.Â Keywords: Organizational Commitment, Job Satisfaction, Productivity